Analisis Biplot Untuk Mendeskripsikan Ciri-Ciri Kecamatan-Kecamatan di Kabupaten Jember - Dewi, Yuliani Setia; Andayani, Nonik (Jurusan Matematika FMIPA Universitas Jember, 2015)
This research aims to describe subdistricts’ characteristics in Jember districts based on society prosperity indicators by using biplot analysis. Biplot analysis is the method of analysis presenting position of n relative object of observation with p variable simultaneously in two dimensions. Biplot analysis with exploration approach through a concept of object relative distance and variable, can be made as suggestions to develop subdistricts in achieving society prosperity. From the result of biplot analysis, it can be obtained that there is a correlation of each society prosperity indicators. According to subdistrict’s characteristics, it can be known about change happened, that is if family planning programme is success for certain subdistricts in the year of 2000, so family planning programme has spread almost throughout all subdistricts in the year of 2001.